The Faint Globular Cluster in the Dwarf Galaxy Andromeda I. (5th September 2017) - Caldwell, Nelson; Strader, Jay; Sand, David J.; Willman, Beth; Seth, Anil C.
Abstract: Observations of globular clusters in dwarf galaxies can be used to study a variety of topics, including the structure of dark matter halos and the history of vigorous star formation in low-mass galaxies. We report on the properties of the faint globular cluster ( M V −3.4) in the M31 dwarf galaxy Andromeda I. This object adds to the growing population of low-luminosity Local Group galaxies that host single globular clusters.